Investigation heavy metals levels in eyebrows cosmetic in Birjand: study of lead and cadmium levels (2017) - Maryam khodadadi; Hadigheh Dorri; Abbas Ali Ramazani; Marziyeh Edalatian; Aghdas Maleki; Zahra Assari (مجله دانشگاه علوم پزشکی بیرجند, 2019)
Background and Aim: Heavy metals such as lead and cadmium are toxic and carcinogenic compounds that are absorbed through the skin. Therefore, the aim of this study was to determine the amount of lead and cadmium heavy metals in bulk branded cosmetic bags (mascara and tattoo) distributed in Birjand. Materials and Methods: In this descriptive-analytical study, by referring to the Birjand cosmetics and health center :::::union::::: and by using a simple random sampling method, the 12 centers are selected and by referring to them, 63 samples of mascara and eyebrow tattoos were selected. Due to the limited number of eyebrow cosmetics brands, all existing brands were sampled. The lead and cadmium levels of the samples were determined using acid digestion and atomic absorption. Data were analyzed using statistical tests of Kruskal-Wallis and Mann-Whitney. Results: The mean lead concentration in mascara and tattoos was 51.8-227.4 μg / g and 37.5 ± 313.6 mg / g, respectively, and in all samples, the concentration of cadmium was zero. There was a significant difference among the different tattoo samples in terms of concentration of lead (P<0.05), but there was no significant difference between mascara samples (P=0.761). Conclusion: Due to unauthorizedness, the concentration of lead heavy metal in conventional cosmetic products and also no significant difference among famous brands, sufficient awareness of the risk of large amounts of such substances is necessary.